Innegligible musculoskeletal disorders caused by zoledronic acid in adjuvant breast cancer treatment: a meta-analysis - Zhou, Wen-Bin (BioMed Central, 2011)
BACKGROUND: Zoledronic acid (ZOL) is widely used for preventing bone loss in early breast cancer patients. However, the adverse effects caused by ZOL itself should not be neglected. Musculoskeletal disorders were common after ZOL administration and distressing to the patients. Up to now, no precise estimation of musculoskeletal disorders has been made. METHODS: Relevant randomized clinical trials were selected by searching the electronic database PubMed, and a meta-analysis was conducted. RESULTS: Four trials reported musculoskeletal disorders of ZOL treatment versus no ZOL, including 2684 patients treated with ZOL and 2712 patients without ZOL treatment. Compared to patients without ZOL treatment, patients treated with ZOL had a significantly higher risk of arthralgia (risk ratio (RR): 1.162, 95% confidence interval (CI): 1.096-1.232, P = 0.466 for heterogeneity) and bone pain (RR: 1.257, 95% CI: 1.149-1.376, P = 0.193 for heterogeneity). Three clinical trials reported the complications of upfront versus delayed ZOL treatment, including 1091 patients with upfront ZOL and 1110 patients with delayed ZOL. The rate of bone pain in upfront group (119/824) was significantly higher than that in delayed group (74/836) (RR: 1.284, 95% CI: 1.135-1.453, P = 0.460 for heterogeneity). CONCLUSIONS: Our meta-analysis suggested that treatment with ZOL was significantly associated to the occurrence of arthralgia and bone pain. Moreover, higher rate of bone pain was observed in patients treated with upfront ZOL compared with delayed ZOL treatment. More attentions should be paid to patients treated with ZOL, especially for immediate ZOL. For patients with low risk of osteoporosis, immediate ZOL may be not needed due to additional musculoskeletal disorders and little benefit. Or it can be stopped after the occurrence of these adverse events.